According to Kolcaba's theory comfort increases the peace of mind of operating room nurses - Dendy Dwi Wahendra; Tri Johan Agus Yuswanto; Marsaid Marsaid; Tri Anjaswarni (Jurnal Keperawatan)
Background: Peace of mind is a psychological state of inner calm and stability that is essential for maintaining the mental health of nurses, especially those working in high-stress environments such as operating rooms. Disruptions in mental peace can impair concentration and affect the quality of care provided. Based on Kolcaba's theory, comfort plays a crucial role in enhancing psychological well-being, including peace of mind. Objectives: This study aims to analyze the relationship between perceived comfort and the level of peace of mind among operating room nurses. Methods: A correlational study with a cross-sectional design was conducted on operating room nurses. Data were collected using standardized questionnaires measuring comfort and peace of mind. The Spearman's rho test was employed to determine the relationship between the two variables. Results: The statistical analysis revealed a significant positive correlation between comfort and peace of mind (Spearman’s rho = 0.477, p = 0.008). This indicates that higher levels of comfort are associated with greater mental tranquility among operating room nurses. Conclusion: Comfort has a significant and positive relationship with peace of mind in operating room nurses. Efforts to improve nurses’ comfort may contribute to better psychological stability and enhance the quality of care in surgical settings.